The Influence of an Acute Bout of Whole Body Vibration on Human Postural Control Responses. Issue 5 (3rd September 2018) - Wilson, Samuel J.; Williams, Charles C.; Gdovin, Jacob R.; Eason, John D.; Luginsland, Lauren A.; Hill, Christopher M.; Chander, Harish; Wade, Chip; Garner, John C.
ABSTRACT: The use of vibrating platforms has become increasingly available, and popular at sports and rehabilitation institutes. Given the discrepancies in the literature regarding whole body vibration (WBV) and human reflexive responses, the purpose of this study was to examine the acute effects of WBV on postural response latencies, as well as associated electromyography measures of the lower extremities during balance perturbations. Reflexive responses during backward and forward balance perturbations were examined before, after, and 10 min after a bout of WBV. The findings suggest that following an acute bout of whole body vibration, muscle activity of the lower extremities is decreased during a reflexive response to an unexpected perturbation, and may be associated with faster reaction time.